Redescription of Sartoriana trilobata (Alcock, 1909) (Crustacea: Decapoda: Brachyura: Gecarcinucidae) from Assam, Northeast India, with notes on the morphology of male gonopods - Chetia, Awarlin; Mitra, Santanu; Das, Debangshu Narayan (Zootaxa, 2021)
Sartoriana trilobata is a species of freshwater crab which occurs exclusively in some areas of Northeast India. Being a riverine crab, it is occasionally found in beels or other riverine wetland habitats formed by monsoon floods in the Brahmaputra basin.The earlier descriptions of this species were mostly incomplete which lacked information on the morphology of the male gonopods.Therefore including the male gonopods, all the morphological features of Sartoriana trilobata are redescribed and illustrated. This species differs considerably from its only congener i.e., Sartoriana spinigera through suits of carapace, chelipeds, gonopods dissimilarities.